Glial pathology in a novel spontaneous mutant mouse of the Eif2b5 gene: a vanishing white matter disease model. Issue 1 (28th October 2019) - Terumitsu‐Tsujita, Mika; Kitaura, Hiroki; Miura, Ikuo; Kiyama, Yuji; Goto, Fumiko; Muraki, Yoshiko; Ominato, Shiho; Hara, Norikazu; Simankova, Anna; Bizen, Norihisa; Kashiwagi, Kazuhiro; Ito, Takuhiro; et al.
Abstract: Vanishing white matter disease (VWM) is an autosomal recessive neurological disorder caused by mutation(s) in any subunit of eukaryotic translation initiation factor 2B (eIF2B), an activator of translation initiation factor eIF2. VWM occurs with mutation of the genes encoding eIF2B subunits ( EIF2B1, EIF2B2, EIF2B3, EIF2B4, and EIF2B5 ). However, little is known regarding the underlying pathogenetic mechanisms or how to treat patients with VWM. Here we describe the identification and detailed analysis of a new spontaneous mutant mouse harboring a point mutation in the Eif2b5 gene (p.Ile98Met). Homozygous Eif2b5 I98M mutant mice exhibited a small body, abnormal gait, male and female infertility, epileptic seizures, and a shortened lifespan. Biochemical analyses indicated that the mutant eIF2B protein with the Eif2b5 I98M mutation decreased guanine nucleotide exchange activity on eIF2, and the level of the endoplasmic reticulum stress marker activating transcription factor 4 was elevated in the 1‐month‐old Eif2b5 I98M brain. Histological analyses indicated up‐regulated glial fibrillary acidic protein immunoreactivity in the astrocytes of the Eif2b5 I98M forebrain and translocation of Bergmann glia in the Eif2b5 I98M cerebellum, as well as increased mRNA expression of an endoplasmic reticulum stress marker, C/EBP homologous protein. Disruption of myelin and clustering of oligodendrocyte progenitor cells were also indicated in the white matter of the Eif2b5 I98M spinal cord at 8 months old. Our data show that Eif2b5 I98M mutants are a good model for understanding VWM pathogenesis and therapy development. Cover Image for this issue: doi: 10.1111/jnc.14751 . Abstract : Schematic of wild‐type and toy mutant mice. In wild‐type mice, global translation is up‐regulated via GEF activity of eIF2B complex. In integrated stress response (ISR) condition, global translation is down‐regulated via decreased GEF activity of eIF2B complex by direct binding of phosphorylated eIF2, which is an inhibitor of eIF2B complex. Up‐regulated translation of ATF4 transcription factor by readthrough of upper open reading frame (uORF) initiates negative feedback pathway, which results in decrease of phosphorylated eIF2. Toy mutant mice have a point mutation in Eif2b5 gene, which results in missense mutation (I98M) and decreased GEF activity of eIF2B complex. In toy mice, Up‐regulated translation of ATF4 transcription factor is also observed. Cover Image for this issue: doi: 10.1111/jnc.14751 .